Zinc deficiency is associated with gynecologic cancer recurrence - Nakanishi, Kazuho; Toyoshima, Masafumi; Ichikawa, Go; Suzuki, Shunji (Frontiers in Oncology, 2022)
Zinc deficiency can cause various symptoms, including hair loss, anemia, and taste disorders. Recently, the association between cancer and zinc deficiency has received much attention with respect to its antioxidant properties. However, only a few studies have investigated the association between gynecologic cancers and zinc; to date, no studies have evaluated serum zinc status at the onset of gynecologic cancer or the relationship between zinc and cancer recurrence. The objectives of the present study were to determine whether serum zinc concentrations are associated with the development of gynecologic cancer, to clarify serum zinc dynamics between the onset and recurrence of gynecologic cancer, and to identify the associated factors. Accordingly, we retrospectively determined serum zinc concentrations before treatment in gynecologic patients with benign disease or cancer at the Nippon Medical School Chiba Hokusoh Hospital. We investigated anemia and hypoalbuminemia—the most common causes of zinc deficiency—as indicators of hyponutrition to determine the causal relationship of this deficiency with chemotherapy, radiation therapy, and recurrence, which may affect zinc concentration during cancer recurrence. The results indicated that there was no difference in zinc concentration between preoperative cancer patients and noncancer patients and that serum zinc concentrations were not associated with developing gynecologic cancers. However, patients with gynecologic cancer exhibited significantly lower serum zinc concentrations following treatment, and patients with recurrent cancer were 4.8 times more likely to develop zinc deficiency than those with nonrecurrent cancer. A serum zinc concentration of <61 μg/dL was an independent predictor of recurrence. Once zinc deficiency occurred, the recurrence rate of zinc deficiency reached as high as 69%. Overall, our study indicates that zinc deficiency is associated with recurrence in gynecological cancers and physicians should monitor zinc levels during disease management.